Evaluation of the association of single nucleotide polymorphisms in the PRPH2 gene with adult-onset foveomacular vitelliform dystrophy. (2nd July 2016) - Grunin, Michelle; Tiosano, Liran; Jaouni, Tareq; Averbukh, Edward; Sharon, Dror; Chowers, Itay
ABSTRACT: Objective : A minority of patients with adult-onset foveomacular vitelliform dystrophy (AFVD) carry mutations in the PRPH2 gene. This gene is highly polymorphic and it was suggested that single-nucleotide polymorphisms (SNPs) in PRPH2 may also be associated with AFVD. We aimed to evaluate for such an association. Methods : A single center cohort from a tertiary referral center including 52 consecutive patients with a clinical diagnosis of AFVD and 91 unaffected individuals was assessed. Sanger sequencing was performed for the PRPH2, BEST1, and IMPG1/2 genes. Investigation as to the frequency of minor alleles for SNPs in PRPH2 was performed and compared to HapMap and Exome Variant Server (EVS) data. Results : None of the patients carry a mutation in PRPH2, BEST1, or IMPG1/2 . Five of 14 known SNPs (rs835, rs361524, rs434102, rs425876, rs390659) in exon 3 of PRPH2 were identified in AFVD patients. A high frequency and percentage of minor alleles of these five SNPs was found in the Israeli AFVD patients and controls compared with European, Chinese, Japanese and African populations identified via HapMap and EVS ( p < 0.05). Power calculation suggested that the sample size was sufficient (80%) to rule out an association with an odds ratio above 2.5. Conclusions : These results suggest that genetic variants in PRPH2 do not compose a major genetic risk factor for AFVD. The Israeli population shows a higher percentage of minor allele frequencies in SNPs in the PRPH2 gene, as compared with other populations. This emphasizes the need for appropriate genetic background when performing SNP association testing.